Peripheral blood mononuclear cells from neovascular age-related macular degeneration patients produce higher levels of chemokines CCL2 (MCP-1) and CXCL8 (IL-8) - Lechner, Judith (J Neuroinflammation, 2017)
BACKGROUND: Infiltrating immune cells including monocytes/macrophages have been implicated in the pathogenesis of neovascular age-related macular degeneration (nAMD). The aim of this study was to investigate the cytokine and chemokine expression and secretion profile of peripheral blood mononuclear cells (PBMCs) from nAMD patients and the relationship between the cytokine/chemokine expression profile and clinical phenotype of nAMD, including macular fibrosis, macular atrophy or the responsiveness to anti-VEGF therapy. METHODS: One hundred sixty-one nAMD patients and 43 controls were enrolled in this study. nAMD patients were divided into subgroups based on the presence/absence of (1) macular atrophy, (2) macular fibrosis and (3) responsiveness to anti-VEGF therapy; 25–30 ml of peripheral blood were obtained from all participants and 5 ml were used for serum collection, and the remaining were used for PBMC isolation using density gradient centrifugation. Intracellular cytokine expressions by PBMCs following phorbol 12-myristate 13-acetate (PMA) and ionomycin stimulation were examined using flow cytometry. Cytokine productions in lipopolysaccharides (LPS)-or 1% oxygen -treated PBMC were measured using cytometric bead array (CBA) assay. In addition, cytokine and chemokine levels in the serum were also measured by CBA assay. RESULTS: PBMCs from nAMD patients secreted higher levels of IL-8, CCL2 and VEGF, especially following LPS and 1% oxygen stimulation, than those from controls. 60~80% of IL-8 producing cells were CD11b(+)CD3(−) monocytes. The percentage of CD11b(+)CD3(−) IL-8(+) was significantly increased in nAMD patients compared to controls. PBMCs from nAMD patients without macular fibrosis produced the highest levels of IL-8 and CCL2, whilst PBMCs from nAMD patients with macular atrophy produced highest levels of VEGF. In addition, PBMCs from patients who partially responded to anti-VEGF produced higher levels of IL-8 compared to the cells from complete responders. Interestingly, serum level of CCL2 was not increased in nAMD patients although there was a trend of increased IL-8 in nAMD patients. CONCLUSIONS: PBMCs, in particular monocytes, may contribute to CNV development in nAMD through secreting elevated levels of IL-8, CCL2 and VEGF after they are recruited to the macula. Apart from VEGF, IL-8 and CCL2 may be additional targets for nAMD management. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-017-0820-y) contains supplementary material, which is available to authorized users.